Guidelines for the Development of Child Development Center Management According to the Operational Standards of Child Development Centers under the Local Government Organizations in Kamphaeng Phet Province - Akkahart, Gittiya; Poomkong , Somsak; Siripoonyanan , Tanasak (Journal of Buddhist Education and Research (JBER), 2025)
This mixed-methods study aimed to (1) assess the current, desired, and needed conditions for managing child development centers in accordance with the operational standards of local administrative organizations in Kamphaeng Phet Province, and (2) propose guidelines for improvement. The sample comprised 344 heads and teachers of child development centers, selected via stratified and simple random sampling based on Krejcie and Morgan’s table. Research instruments included a five-point Likert scale questionnaire, semi-structured interview protocols, and evaluation forms to assess the appropriateness and feasibility of the proposed guidelines. Data were analyzed using descriptive statistics (percentages, means, standard deviations), the Modified Priority Needs Index (PNImodified), and content analysis. The results indicated the following: 1. The current management conditions were rated at a high level overall (x̄ = 4.05), with academic and curriculum-based activities receiving the highest score (x̄ = 4.13), and infrastructure, environment, and safety the lowest ( x̄ = 4.00). 2. The desired conditions were rated at the highest level overall ( x̄ = 4.87), with the promotion of early childhood development networks receiving the highest score ( x̄ = 4.94), and center management the lowest (x̄ = 4.80). 3. The prioritized needs, based on PNImodified values, were as follows: promotion of early childhood development networks (0.233), academic and curriculum-based activities (0.223), participation and support (0.216), personnel (0.181), center management (0.180), and infrastructure, environment, and safety (0.180). 4. The proposed development guidelines encompassed six domains, each with three strategies, totaling 18 strategies. The appropriateness (x̄ = 4.77) and feasibility ( x̄ = 4.68) of the guidelines were both rated at the highest level.